About gorillas, compensations, blindness and salaries: Why the bank can make use of my compensation account - Gómez Ramos, Carlos Andrés (2020)
In Peru, there is no clear and uniform criteria to solve cases regarding charges made by financial institutions to customers’ compensation accounts as a means of compensation for debts incurred by the user. In the last ten years, different instances from the Indecopi and Supreme Court have issued contradictory rulings, evidencing a lack of consensus about the legality or illegality of said charges. Faced with this reality, the author wishes to show how the fixation on certain aspects of these cases have made jurists develop inattentional blindness, which lead them to base their reasoning on false premises. With this article, the author hopes to correct this mistake. In order to achieve this, he analyzes what is the duty of care, the difference between the concept of compensation and automatic debit, and, finally, the real disposable nature of remunerations. Thus, he highlights the aspects associated with charges made by financial institutions to customers’ accounts that are usually overlooked by the courts.